1987
DOI: 10.1111/j.1559-3584.1987.tb01395.x
|View full text |Cite
|
Sign up to set email alerts
|

The U.S. Naval Academy's New Yard Patrol Craft: From Concept to Delivery

Abstract: The design of the new 108‐ft yard patrol craft (YPs) for the U.S. Naval Academy is described from its beginnings as a senior midshipman design project, through its preliminary and contract design development at the U.S. Navy's small craft design team headquarters, Naval Sea Combat Systems Engineering Station, Norfolk, Virginia (NAVSEACOMBATSYSENGSTA‐Norfolk). During preliminary and contract design the Naval Academy Hydromechanics Laboratory (NAHL) provided experimental data to support NAVSEA‐COMBATSYSENGSTA‐No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…At all course levels, instructors incorporate laboratory and field work, as appropriate, including rotating tank experiments (e.g., Illari et al, 2009) and observational measurements taken from short cruises in Chesapeake Bay on our Yard Patrol craft (Compton et al, 1987). A detailed description of each department course is available at http://www.usna.…”
Section: Oceanography Curriculummentioning
confidence: 99%
“…At all course levels, instructors incorporate laboratory and field work, as appropriate, including rotating tank experiments (e.g., Illari et al, 2009) and observational measurements taken from short cruises in Chesapeake Bay on our Yard Patrol craft (Compton et al, 1987). A detailed description of each department course is available at http://www.usna.…”
Section: Oceanography Curriculummentioning
confidence: 99%
“…During these trials, the YP showed herself to be highly maneuverable and stable. This, combined with the effectiveness of the noise control measures, resulted in a very comfortable boat" [15]. Noise and vibration data taken on the 80-ft. YPs, combined with expected source level changes, were used to predict that the noise criteria would be exceeded by approximately 10 to 15 dB.…”
Section: Noise Control Programmentioning
confidence: 99%